Phenotypic and molecular characterization of Pantoea stewartii subspecies stewartii causing bronzing disease of jackfruit (Artocarpus heterophyllus) in Maran region - Mohd Zakiyuddin, Muzainah (2017)
Jackfruit (Artocarpus heterophyllus) is one of the most widely grown fruit crop in Malaysia. Under the Third National Agricultural Policy, it has been recognized as having the potential to meet domestic demand, especially for export and as a replacement for imports. Fruit bronzing disease caused by the bacterium Pantoea stewartii subspecies stewartii (P. stewartii subsp. stewartii) is frequently found in jackfruit, which eventually leads to production loss. The disease is characterized by yellowish- orange to reddish discoloration of the affected pulps and rags in the fruit. Once infected, the fruit quality is compromised and could discourage the consumers and processors. The objectives of this study are; 1) to isolate and identify P. stewartii subsp. stewartii in local jackfruit varieties using phenotypic characterization and 2) to determine the genetic relationship of P. stewartii subsp. stewartii strains isolated via molecular identification and phylogenetic analyses. In January 2017, symptoms of infected jackfruit with bronzing were observed in Ladang Taman Kekal Pengeluaran Makanan (TKPM) Serengkam, Maran Pahang region. To identify the pathogen, 8 disease fruits resembled bronzing symptom were collected from the field by randomly to the disease, excised and cultured onto nutrient agar (NA) medium and incubater overnight at 350C. Two representative bacteria colonies were obtained and selected for further characterization. Bacteria colonies were yellow-pigment, round, smooth and translucent. All strains were Gram-negative rod- shaped, positive for Kovac oxidase and catalase tests and negative for potassium hydroxide (KOH) reaction. These are characteristics of Pantoea spp. For the pathogenicity test, 10 ml of 108 CFU/ml bacterial suspension of four selected strains were injected into healthy detached jackfruits of J33 (Tekam Yellow) variety. Fruits that were infiltrated with sterile distilled water served for negative control. Inoculations with all strains were performed in two replications, as well as the uninoculated control detached fruits. The inoculated fruits produced bronzing symptoms as observed on naturally diseased samples. Besides that, control fruits remained asymptomatic. Strain culture were re-isolated and showed the morphological and biochemical characteristics as previously described. The PCR amplification of 16S rDNA 8F and 1492R primer set produced a 1400 bp amplicon in each strain. To our knowledge, this is the first report of bronzing disease caused by P. stewartii subsp. stewartii in jackfruit in Malaysia.